A review of local construction practices applied on unreinforced adobe buildings in South America - Cocco, Giulia; Brando, Giuseppe; Spacone, Enrico (Frontiers in Built Environment, 2022)
The historical earthquake activity that involved Andean countries in the last centuries makes the seismic risk evaluation associated to buildings in these areas an issue of crucial concern. Planning seismic risk mitigation policies requires an extensive knowledge of the territorial built environment, of the adopted construction techniques and of the adopted anti-seismic presidiums, in particular when applied during the reconstruction processes carried out after destructive events of the past. In this perspective, this paper contributes to the analysis of adobe vernacular buildings, which represent a spread typology in Latin America and the Caribbean, stressing the past construction practices, their fragilities, and the mitigation measures applied till today. To this purpose, the city center of Cusco, in Peru, where residential buildings are mostly made of adobe, is considered as a meaningful field of observation, because of the long history of the center, which allows to recognize also old construction techniques and the additions/raisings applied during the buildings life, as well as due to the relevant historical seismicity, which permits to appreciate the reconstruction processes implemented after seismic events occurred in the past.